2020
DOI: 10.1186/s13018-020-01906-0
|View full text |Cite
|
Sign up to set email alerts
|

How the clinical dosage of bone cement biomechanically affects adjacent vertebrae

Abstract: Objective: This study evaluated the biomechanical changes in the adjacent vertebrae under a physiological load (500 N) when the clinically relevant amount of bone cement was injected into fractured cadaver vertebral bodies. Methods: The embalmed cadaver thoracolumbar specimens in which each vertebral body (T12-L2) had a BMD of < 0.75 g/cm 2 were used for the experiment. For establishing a fracture model, the upper one third of the L1 vertebra was performed wedge osteotomy and the superior endplate was kept com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Theoretically, bone cement might increase the pressure on the adjacent disk, resulting in the deformation of the adjacent endplate, causing fractures in the endplate and nearby cancellous bone. Thus, stress and strain changes can further exacerbate, ultimately leading to adjacent vertebral fractures [ 21 ]. In the present study, when the Cobb angle was large, the fracture rate of the dissected vertebral body was higher, and PVP was higher than PKP.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, bone cement might increase the pressure on the adjacent disk, resulting in the deformation of the adjacent endplate, causing fractures in the endplate and nearby cancellous bone. Thus, stress and strain changes can further exacerbate, ultimately leading to adjacent vertebral fractures [ 21 ]. In the present study, when the Cobb angle was large, the fracture rate of the dissected vertebral body was higher, and PVP was higher than PKP.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Other studies have shown that large bone cement dosages do not show greater benefits and lead to asymmetrical cement distribution and excessive vertebral stiffness. 6 , 8 , 20 , 21 In some cases, even if the injection volume of bone cement was increased, bone cement was an uncertainly connected endplate, indicating that the amount of bone cement is not the decisive factor in improving the distribution pattern. 23 , 24 Based on these findings, we explored a new approach.…”
Section: Discussionmentioning
confidence: 99%
“… 5 A mismatch between mechanical properties of fractured bone and nonfractured bone may be partially reversed by the addition of an adequate amount of BC and may result in less abnormal strain on the adjacent vertebral bodies. 13 …”
Section: Acrylic Bone Cementsmentioning
confidence: 99%
“…5 A mismatch between mechanical properties of fractured bone and nonfractured bone may be partially reversed by the addition of an adequate amount of BC and may result in less abnormal strain on the adjacent vertebral bodies. 13 When engineering ABCs, cement viscosity is one of the most important characteristics. The viscosity of the cement affects injectability, leakage, retention in the vertebral body, and the final mechanical properties of the set cement.…”
Section: Acrylic Bone Cementsmentioning
confidence: 99%